Answer:
Final answer is choice a). ![-17-9n](https://tex.z-dn.net/?f=-17-9n)
Step-by-step explanation:
Given expression is
![-7\left(2+n\right)+\frac{1}{3}\left(-9-6n\right)](https://tex.z-dn.net/?f=-7%5Cleft%282%2Bn%5Cright%29%2B%5Cfrac%7B1%7D%7B3%7D%5Cleft%28-9-6n%5Cright%29)
![=-14-7n+\frac{1}{3}\left(-9-6n\right)](https://tex.z-dn.net/?f=%3D-14-7n%2B%5Cfrac%7B1%7D%7B3%7D%5Cleft%28-9-6n%5Cright%29)
![=-14-7n-3-2n](https://tex.z-dn.net/?f=%3D-14-7n-3-2n)
![=](https://tex.z-dn.net/?f=%3D)
![=-14-3-7n-2n](https://tex.z-dn.net/?f=%3D-14-3-7n-2n)
![=-17-9n](https://tex.z-dn.net/?f=%3D-17-9n)
Hence final answer is choice a). ![-17-9n](https://tex.z-dn.net/?f=-17-9n)
Answer: 33
Step-by-step explanation: In the problem, you are given the figure with the following:
2x+3 and 3x+12
Method: Lets set this into an equation. Remember that straight lines add up to 180°.
2x+3+3x+12=180° Combine like terms.
5x+15=180°
5x=165°
x=33°
You can always plug in 33° in the expression that was set to make sure it does give you 180°.
Hope this helps.
TO write the function into vertex form, we need to add one zero and the solution is shown below:
f(x)= x² -6x +1
Add one zero in the form of -9 and 9, such as:
f(x) = x² -6x +1 -9 +9
f(x) = (x² -6x +9) +(1-9)
f(x) = (x-3)² + (-8)
f(x) = (x-3)² - 8
This is the vertex form of the given function and only one zero is being added.
Answer:
x>10
Step-by-step explanation:
Answer:
21-2x
Step-by-step explanation:
11-2(x-5)
11-2x+10
21-2x
not completely sure if im right... if i am can you mark me brainliest